Simulation Of Convective Heat Transfer Coefficient In The Receiver Tube Of A Parabolic Trough Concentrator. - Sulaiman, Fauziah; Mahinder Singh, Balbir Singh (2003)
The evaluation of the convective heat transfer coefficient, hc by simulation can be made simple, if modeling of the temperature dependent parameters is carried out effectively. Usually Reynolds, Prandtl and Nusselt numbers are used to compute the convective heat transfer coefficient.